Negotiating the struggle for justice negotiation and communication practices of selected families of media killings - Ragragio, Jefferson Lyndon D. (2016)
Access online through this link: https://www.plarideljournal.org/article/negotiating-struggle-justice-negotiation-communication-practices-selected-families-media-killings
Keywords: Crimes against journalists; Crime in mass media; Negotiation